Neuroprotective properties of cannabinoids in cellular and animal models : hypotheses and facts - Udovin, Lucas Daniel (2020)
Fil: Udovin, Lucas Daniel. Universidad de Buenos Aires. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones Cardiológicas; Argentina